Combined Biosynthetic Pathway Engineering and Storage Pool Expansion for High-Level Production of Ergosterol in Industrial Saccharomyces cerevisiae - Sun, Zhi-Jiao; Lian, Jia-Zhang; Zhu, Li; Jiang, Yi-Qi; Li, Guo-Si; Xue, Hai-Long; Wu, Mian-Bin; Yang, Li-Rong; Lin, Jian-Ping (Frontiers in Bioengineering and Biotechnology, 2021)
Ergosterol, a terpenoid compound produced by fungi, is an economically important metabolite serving as the direct precursor of steroid drugs. Herein, ergsosterol biosynthetic pathway modification combined with storage capacity enhancement was proposed to synergistically improve the production of ergosterol in S. cerevisiae. S. cerevisiae strain S1 accumulated the highest amount of ergosterol (7.8 mg/g DCW) among the wild-type yeast strains tested and was first selected as the host for subsequent metabolic engineering studies. Then, the push and pull of ergosterol biosynthesis were engineered to increase the metabolic flux, overexpression of the sterol acyltransferase gene ARE2 increased ergosterol content to 10 mg/g DCW and additional overexpression of a global regulatory factor allele (UPC2-1) increased the ergosterol content to 16.7 mg/g DCW. Furthermore, considering the hydrophobicity sterol esters and accumulation in lipid droplets, the fatty acid biosynthetic pathway was enhanced to expand the storage pool for ergosterol. Overexpression of ACC1 coding for the acetyl-CoA carboxylase increased ergosterol content from 16.7 mg/g DCW to 20.7 mg/g DCW. To address growth inhibition resulted from premature accumulation of ergosterol, auto-inducible promoters were employed to dynamically control the expression of ARE2, UPC2-1, and ACC1. Consequently, better cell growth led to an increase of ergosterol content to 40.6 mg/g DCW, which is 4.2-fold higher than that of the starting strain. Finally, a two-stage feeding strategy was employed for high-density cell fermentation, with an ergosterol yield of 2986.7 mg/L and content of 29.5 mg/g DCW. This study provided an effective approach for the production of ergosterol and other related terpenoid molecules.